Safeguarding amateur athletes: An examination of player welfare among senior inter-county Gaelic players - Elish Kelly; Conor Keegan; Brendan Walsh (The Economic and Social Research Institute (ESRI), 2019)
This research finds that GAA commitments influence education, career and other aspects of senior inter-county players' lives. The study was commissioned by the GAA and the GPA. Gaelic players are highly educated, with 61 per cent having at least a university degree compared to 35 per cent of the general male population of the same age. However, the study finds that players appear to be basing many decisions related to their education and their professional career around playing Gaelic games. The report is the second ESRI study to examine how the commitment levels of the amateur sports affect players' lives. This report also examines a range of other issues relevant to players' lives, including alcohol consumption, supplement use, their views on player welfare supports and their experiences within the inter-county set-up.
Keywords: 330